Comparing incidental vocabulary learning from reading-only and reading-while-listening. (April 2021) - Chen, Yingzhao
Abstract: This study compares incidental vocabulary learning in reading-while-listening and reading-only conditions. Using both offline and online outcome measures, I assessed explicit form and meaning knowledge and the lexicalization of new words. I also explored how L2 listening and reading proficiency moderated learning gains in the two treatment conditions. L2 learners first read or read-while-listened to four short stories in English for meaning, with embedded target vocabulary items. They then completed surprise vocabulary posttests in the order of a form priming lexical decision task, a form recognition test, a form-meaning connection test and a semantic priming lexical decision task. Results showed that while the reading-while-listening group outperformed the reading-only group in recognizing the form and meaning of the target vocabulary, neither group fully lexicalized the new words, which was crucial for fluent lexical retrieval. L2 listening and reading proficiency affected learning from reading-while-listening and reading-only differentially: the reading-while-listening group was negatively affected by L2 reading proficiency when controlling for listening proficiency while performance of the reading-only group was not predicted by L2 proficiency. Implications for the use of bimodal input in incidental vocabulary learning are discussed.